Physical Quality and pH of Chicory Silase (Cichorium Intybus L) and Onggok with the Addition of Tannins as Additives - Nawang Wulan, Dyah; Hidayat, Rahmat; Mayasari, Novi; Budiman, Atun; Rizki Yanza, Yulianri; Ariana Setiawan, Muhammad (Riviera Publishing, 2024)
This study aims to examine the effect of the addition of tannins as additives on the physical quality of chicory mixed silage (Cichorium intybus L.) and onggok. The method used was a Complete Random Design (RAL) consisting of 5 treatments and 5 replicates. The treatment used consisted of P0(-) (100% onggory without the addition of tannins), P1(+) (100% onggok + 12 grams of tannins), P2 (chicory 75% + 25% onggok + tannin 12 grams), P3 (chicory 50% + onggok 50% + tannins 12 grams), P4 (chicory 25% + onggok 75% + tannins 12 grams). The data was analyzed by Kruskal Wallis analysis, if there was a real difference, the Dunn test was continued. The results showed that tannins significantly improved the physical quality of silage with parameters in the form of color, aroma, texture, the presence of mold, and pH. Chicory increases the nutrient content, while tannins play the role of special antibacterial and antifungal agents that can make bacteria and fungi brittle. This makes silage have a longer shelf life for the effectiveness of ruminant feed.